Penerapan Akuntansi Keberlanjutan Berbasis ESG dalam Pengidentifikasian Tanggung Jawab Lingkungan pada Dinas Pekerjaan Umum Bina Marga Kota Surabaya - Elisabeth Lauboling; Marlinda Ina; Sirilia S.J Ruben; Titiek Rachmawati (Jurnal Manajemen dan Ekonomi Kreatif, 2026)
The implementation of Environmental, Social, and Governance (ESG)-based sustainability accounting is gaining increasing attention in the public sector as an effort to strengthen transparency and accountability, particularly in environmental management. This study aims to examine how ESG-based sustainability accounting is applied in identifying environmental responsibilities at the Surabaya City Public Works and Highways Agency. The research used a qualitative approach, with data collection methods including interviews, observations, and documentation studies.  The research findings indicate that the application of ESG principles in financial management and operational activities is still in its early stages of development, particularly in environmental reporting. Efforts to identify environmental responsibilities have been implemented through various sustainable development programs, but they have not been optimally integrated into the existing accounting system. Several obstacles encountered include limited technical regulations, a lack of competent human resources, and the absence of uniform reporting standards. Therefore, strengthening policies and developing an ESG-based accounting system is necessary to enhance environmental accountability and support sustainable infrastructure development in Surabaya.